Structure and evolution of the drainage system of a Himalayan debris-covered glacier, and its relationship with patterns of mass loss - Benn, Douglas I.; Thompson, Sarah; Gulley, Jason; Mertes, Jordan; Luckman, Adrian; Nicholson, Lindsey (The Cryosphere, 2017)
We provide the first synoptic view of the drainage system of a Himalayan debris-covered glacier and its evolution through time, based on speleological exploration and satellite image analysis of Ngozumpa Glacier, Nepal. The drainage system has several linked components: 1) a seasonal subglacial drainage system below the upper ablation zone; 2) supraglacial channels allowing efficient meltwater transport across parts of the upper ablation zone; 3) sub-marginal channels, allowing long-distance transport of meltwater; 4) perched ponds, which intermittently store meltwater prior to evacuation via the englacial drainage system; 5) englacial cut-and-closure conduits, which may undergo repeated cycles of abandonment and reactivation; 6) a 'base-level' lake system (Spillway Lake) dammed behind the terminal moraine. The distribution and relative importance of these elements has evolved through time, in response to sustained negative mass balance. The area occupied by perched ponds has expanded upglacier at the expense of supraglacial channels, and Spillway Lake has grown as more of the glacier surface ablates to base level. Subsurface processes play a governing role in creating, maintaining and shutting down exposures of ice at the glacier surface, with a major impact on spatial patterns and rates of surface mass loss. Comparison of our results with observations on other glaciers indicate that englacial drainage systems play a key role in the response of debris-covered glaciers to sustained periods of negative mass balance.